Case Report: Complicated Meckel Diverticulum Spectrum in Children - Gunadi,; Damayanti, Wahyu; Saputra, Robin Perdana; Ramadhita,; Ibrohim, Ibnu Sina; Lestiono, Andi; Melati, Devy; Permatahati, Winda Intan; Widowati, Titis; Makhmudi, Akhmad (Frontiers in Surgery, 2021)
Background: Meckel diverticulum (MD) is the most common congenital anomaly of the intestines, with an incidence of 2% of the general population. It can present as various clinical features with complications and be life threatening if diagnosis is delayed and treatment late. Case Presentation: We report three pediatric cases with complicated MD: one female presented with small-bowel obstruction, one male with peritonitis, and one female with severe iron-deficiency anemia, without gross gastrointestinal bleeding nor any ectopic gastric mucosa. All patients underwent exploratory laparotomy, segmental small-bowel resection, and primary anastomosis. They successfully recovered and were uneventfully discharged on the fourth, seventh, and 10th postoperative days, respectively. Conclusions: MD can present with various complication spectrums, including small-bowel obstruction, peritonitis, and severe iron-deficiency anemia, which may cause difficulty in definitive diagnosis, particularly in children. Segmental small-bowel resection and primary anastomosis are effective surgical approaches and show good outcomes for MD patients.